Peningkatan Mutu Organoleptik Terasi Jembret Melalui Perbaikan Kemasan - Helmi Haris; Fitra Mulya Jaya; Anjasmara Anjasmara (JURNAL AGROINDUSTRI HALAL, 2024)
The village of Sungsang is in the Banyuasin II Sub-district, Banyuasin Regency. Its territory lies in a coastal area, and most of its inhabitants are fishermen who engage in traditional fishing activities. One of the distinctive processed seafood products of Sungsang village is Terasi, with one of its variants being Terasi Jembret. Despite Sungsang village's considerable production of processed Terasi, the packaging methods still need to be revised and need more informative compositions, thereby diminishing the attractiveness of Terasi Jembret. This research aims to design a more appealing packaging for Terasi to enhance consumer appeal towards the product. The research methodology employed a Completely Randomized Design (CRD) with four treatment variations in Terasi packaging: P0: traditional polyethylene (PE) packaging, P1: labeled polypropylene (PP) packaging, P2: labeled polypropylene (PP) standing pouch packaging, and P3: labeled aluminum foil standing pouch packaging. The research findings indicate that the panelists prefer treatment P3, namely the labeled aluminum foil standing pouch packaging. Panelists provided high ratings for this packaging, with a likability score of 4.80 (Very likable) for color, 4.80 (Very likable) for appearance, and 4.52 (Very likable) for aroma. Furthermore, the tested parameters comply with the Indonesian National Standard (SNI) for Terasi, with water content at 44.21%, ash content at 1.14%, protein content at 17.75%, and carbohydrate content at 26.30%.